Individual patterns of anadromy determine the cost of salmon lice exposure in brown trout - K. L. Hawley; H. A. Urke; T. Kristensen; T. O. Haugen (Ecosphere)
Abstract Facultative anadromous salmonids may alter migratory behavior to mitigate against detrimental infections of aquaculture‐derived salmon lice (Lepeophtheirus salmonis); however, this likely incurs negative growth and fitness consequences. This flexibility in migratory behavior also creates analytical challenges in estimating lice infestation levels and the consequences of exposure. We utilized simulated individual migration trajectories of facultatively anadromous brown trout (Salmo trutta) (N = 8049), generated from spatial‐temporal fjord‐use models fitted to empirical tracking data (N = 517). These trajectories were superimposed with open‐access spatial‐temporal modeled lice densities. Individual accumulated lice exposure and infestation were simulated over a 6‐month period for smolts and annually for veteran migrant life‐stages. The degree of lice‐induced mortality was estimated according to year (2013–2015), population (N = 5), and life‐stage of brown trout, within a semi‐enclosed fjord system (Sognefjorden, Norway). A gradient of lice was spatially distributed throughout the fjord. Highest densities were modeled in the outer‐fjord at a closer vicinity to aquaculture facilities. Accordingly, estimates of accumulated lice infestation were higher for individuals that underwent long‐distance migrations, residing for longer in the outer‐fjord, with limited differences observed between years. As most brown trout remained in the inner‐fjord, an area protected from aquaculture, individual accumulated levels of lice exposure and infestation were low, resulting in infestation estimates largely below critical‐mortality thresholds. The fraction of total mortality attributed to lice during sea‐sojourn was greater for long‐distance migrants (smolts: 25.3%; veteran migrants: 14.8%) versus those remaining within the inner‐fjord (smolts: 14.7%; veteran migrants: 1.7%). This resulted in an unequal contribution of lice to total mortality among populations (range: 3.3%–34.3%). Despite an equal distribution of lice exposure for all populations within the fjord, diverse mortality consequences among populations were estimated, largely resulting from individual selection of migration trajectory. Therefore, generic models of lice effects on facultative anadromous salmonids should be used with caution. Instead, the application of simulated migration trajectories to incorporate flexible behavior at the individual level is suggested. The findings indicate that Sognefjorden brown trout may have reduced their seaward migration extent to avoid direct mortality from salmon lice. This emphasizes the importance of monitoring and management actions to preserve selection for anadromy.